Carbon aerogel-based cathode for lithium-sulfur batteries

By using sulfide-doped nanopore carbon materials in lithium-sulfur batteries, the problems of high resistance and intermediate dissolution of traditional lithium-sulfur batteries are solved, and higher energy density and cycle life are achieved.

JP7648535B2Active Publication Date: 2025-03-18ASPEN AEROGELS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021558493
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-22
Filing Date
2020-03-22
Publication Date
2025-03-18
Estimated Expiration
2040-03-22

AI Technical Summary

Technical Problem

Traditional lithium-sulfur batteries face high resistance and dissolution of intermediate lithium polysulfides in electrolytes, resulting in poor energy density and cycle life.

Method used

The sulfide-doped nanoporous carbon material is used to form an optimized pore structure and high mechanical strength in the carbon material to ensure the uniform distribution and stability of sulfur to form a binder-free carbon air gel composite.

Benefits of technology

It improves the energy density and cycle life of lithium-sulfur batteries, reduces the dissolution of intermediates in the electrolyte, and enhances the mechanical strength and electrical conductivity of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648535000001
    Figure 0007648535000001
  • Figure 0007648535000002
    Figure 0007648535000002
  • Figure 0007648535000003
    Figure 0007648535000003
Patent Text Reader

Abstract

Nanoporous carbon-based scaffolds or structures, particularly carbon aerogels, and their manufacture and use. Embodiments include sulfur-doped cathode materials in lithium-sulfur batteries, where the cathode is formed from a monolithic, binder-free, polyimide-derived carbon aerogel with a modest current collector. The carbon aerogel contains pores that surround elemental sulfur and accommodate the expansion of sulfur during its conversion to lithium sulfide. The cathode and underlying carbon aerogel provide optimal properties for use in lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Patent Application No. 16 / 826,276, filed March 22, 2020, and U.S. Provisional Patent Application No. 62 / 822,698, filed March 22, 2019, which are incorporated herein by reference in their entireties, and any definitions of terms herein are controlling.

[0002] The present invention relates generally to nanoporous carbon-based materials. More specifically, it relates to carbon aerogels suitable for use in environments involving electrochemical reactions, for example as electrode materials in lithium-sulfur batteries. [Background technology]

[0003] Aerogels are solid materials that contain a highly porous network of micro- and meso-sized pores. Depending on the precursor materials used and the processing performed, the pores of an aerogel can frequently occupy more than 90% of the volume when the density of the aerogel is about 0.05 g / cc. Aerogels are generally created by removing the solvent from the gel (its solvent-containing solid network) so that the shrinkage of the gel can be minimized or not caused at all by capillary forces at its surface. Methods of solvent removal include, but are not limited to, supercritical drying (also drying using a supercritical fluid, such that the low surface tension of the supercritical fluid exchanges with the transient solvent in the gel), exchange of the solvent with a supercritical fluid, exchange of the solvent with a fluid that is subsequently converted to a supercritical state, sub- or near-critical drying, and sublimation of the frozen solvent in a freeze-drying process. See, for example, PCT Patent Application Publication No. 2016127084 (A1). It should be noted that upon drying at ambient conditions, evaporation of the solvent may cause the gel to shrink and a xerogel may form. Thus, the creation of aerogels by sol-gel or other polymerization methods typically proceeds in the following sequence of steps: dissolution of a solute in a solvent, formation of a sol / solution / mixture, formation of a gel (which may include further crosslinking), and removal of the solvent by supercritical drying techniques or any other method that removes the solvent from the gel without causing pore collapse.

[0004] Aerogels can be formed from inorganic and / or organic materials. For example, when formed with organic materials such as phenol, resorcinol-formaldehyde (RF), phloroglucinol furaldehyde (PF), polyacrylonitrile (PAN), polyimide (PI), polyurethane (PU), polybutadiene, polydicyclopentadiene, and their precursors or polymer derivatives, the aerogels can be carbonized (e.g., by pyrolysis) to form carbon aerogels that can have different or overlapping properties (e.g., pore volume, pore size distribution, morphology, etc.) depending on the precursor materials and methodology used. However, in all cases, there were certain deficiencies based on the material and application, such as low pore volume, wide pore size distribution, low mechanical strength, etc. In recent years, efforts have been dedicated to the development and characterization of carbon aerogels as electrode materials with improved performance for applications in energy storage devices such as lithium-sulfur batteries (LSBs).

[0005] LSBs are becoming an increasingly attractive form of electrochemical energy storage and alternative to lithium-ion batteries (LIBs) due to their potential to achieve high reversible energy storage and high cycling at low cost. LSBs are a type of rechargeable battery in which lithium ions move from the anode to the cathode during discharge and from the cathode to the anode during charging. Traditionally, for LSB systems, the anode is formed from lithium metal and the cathode is formed from a carbon-sulfur composite, with elemental sulfur and polysulfides present within the porous structure of the carbon, and a polymer binder is used to maintain the integrity of the composite. Sulfur is an earth-abundant element known to have a high theoretical specific capacity (~1672 mAh / g, an order of magnitude higher than metal oxide cathode materials commonly used in LIBs) when used as the cathode in LSBs.

[0006] Despite the opportunity to achieve ultra-high energy density with LSBs, conventional LSBs have not been widely adopted commercially like their LIB counterparts, which are characterized by higher cycle life but lower energy density. Conventional LSBs suffer from two significant challenges. The first challenge is the high electrical resistivity of sulfur and the formation of Li-S species during discharge. This conversion reaction is called lithium sulfide (Li 2 S), with a volume expansion of as much as 80%. Another major challenge is the solubility or dissolution of intermediate lithium polysulfides in the electrolyte over multiple charge-discharge cycles, ultimately resulting in a reduction in the sulfur available for the necessary conversion reactions during discharge.

[0007] Thus, what is needed is an improved nanoporous carbon material containing functional morphology and optimal pore structure, in which optimal sulfur loading can be achieved and in which the sulfur is trapped in a size consistent environment (e.g., narrow pore size distribution). However, considering the art as a whole at the time this invention was made, it was not apparent to one skilled in the art how the shortcomings of the prior art could be overcome.

[0008] Although certain aspects of the prior art have been discussed to facilitate disclosure of the present invention, applicants have not in any way rejected these technical aspects, and it is contemplated that the claimed invention may include one or more of the prior art technical aspects described herein, particularly in combination with the innovative aspects described herein.

[0009] The present invention may address one or more of the problems and deficiencies of the technology described above. However, it is believed that the present invention may prove useful in addressing other problems and deficiencies in some technical fields. Thus, the claimed invention should not necessarily be construed as being limited to addressing any of the specific problems or deficiencies discussed herein.

[0010] Where a document, act or item of knowledge is referenced or discussed in this specification, such reference or discussion is not an admission that that document, act or item of knowledge, or any combination thereof, was available to the public as of the priority date, was known to the public, was part of the common general knowledge, or constitutes prior art under any applicable legal provision, or is known to be relevant to any attempt to solve any problem to which this specification pertains. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] PCT Patent Application Publication No. 2016127084 Brochure (A1) Summary of the Invention

[0012] The long-standing and heretofore unmet need for improved nanoporous carbon materials is now met by a new, useful and unobvious invention.

[0013] A first general aspect relates to a sulfur-doped nanoporous carbon material. The sulfur-doped nanoporous carbon material includes a pore structure, the pore structure being: Fibril The morphology and series of pores surrounding elemental sulfur.

[0014] A second general aspect is a sulfur-doped nanoporous carbon material comprising: Fibril The present invention relates to a sulfur-doped nanoporous carbon material comprising a pore structure including morphology, a Young's modulus of at least about 0.2 GPa, and a density of about 0.10 g / cc to about 1.5 g / cc. In an exemplary embodiment, the nanoporous carbon material has an electrical conductivity of at least about 1 S / cm.

[0015] A third general aspect is a sulfur-doped nanoporous carbon material comprising: FibrilThe nanoporous carbon material comprises a pore structure including morphology; a conductivity of at least about 1 S / cm; and a density of about 0.10 g / cc to about 1.5 g / cc. In an exemplary embodiment, the nanoporous carbon material has a Young's modulus of at least about 0.2 GPa.

[0016] In an exemplary embodiment, the nanoporous carbon material comprises a carbon aerogel. For example, the carbon material comprises a polyimide-derived carbon aerogel. In certain embodiments, the carbon aerogel may be in monolithic or powder form. In a monolithic embodiment, the carbon aerogel may be in powder form. gel The monolithic carbon can be substantially or completely free of binders. The monolithic carbon can have a thickness of, for example, about 10 μm to about 1000 μm.

[0017] In an exemplary embodiment, the pore structure of the nanoporous carbon material is characterized by pores surrounding the sulfur. For example, the pores form an interconnected structure around the sulfur, characterized by multiple connection points between the sulfur and the pore walls of each pore in which the sulfur is surrounded. The carbon material can be doped with sulfur in an amount of about 5% to about 90% by weight of the carbon material.

[0018] In any embodiment, the carbon material can have a pore volume of at least 0.3 cc / g. In any embodiment, the carbon material can have a porosity of about 10% to about 90%. In any embodiment, the carbon material can have a capacity of about 800 mAh / g to about 1700 mAh / g. In any embodiment, the pore structure of the carbon material comprises a full width at half maximum of about 50 nm or less. In any embodiment, the pore structure comprises a pore size at the largest peak from the distribution of about 100 nm or less. In any embodiment, the nanoporous ...01 cc / g. Fibril The morphology can include an average strut width of about 2-10 nm.

[0019] A further general aspect relates to a sulfur-containing monolithic polyimide-derived carbon aerogel composite formed with a nanoporous carbon material, the composite being binder-free and elemental sulfur is enclosed within the pores of the monolithic polyimide-derived carbon aerogel composite.

[0020] Another general aspect is a current collector for a lithium-sulfur battery that includes an open-cell, monolithic, polyimide-derived nanoporous carbon aerogel having a fibril network and a series of pores, and elemental sulfur surrounded by the series of pores. none , binder none of interconnect cathode materials.

[0021] Exemplary embodiments include an electrode comprising any of the other embodiments of the nanoporous carbon material. For example, the electrode can be a cathode. The cathode can be free of a separate current collector. Further exemplary embodiments include an electrochemical cell or energy storage device comprising any of the other embodiments of the nanoporous carbon material or electrode. For example, the energy storage device can be a battery, such as a lithium-sulfur battery.

[0022] A further general aspect relates to a method for forming a continuous porous carbon-sulfur composite. In an exemplary embodiment, the method includes a method for forming a continuous porous carbon-sulfur composite, the method including providing a polyimide precursor; chemically or thermally imidizing the polyimide precursor; drying the imidized mixture to obtain a continuous porous polyimide; pyrolyzing the porous polyimide to obtain a continuous porous carbon; and incorporating sulfur on or in the continuous porous carbon to obtain a continuous porous sulfur composite having a weight percent sulfur of greater than 0% and less than about 95% and a porosity of about 10% to about 90%.

[0023] In an exemplary embodiment, the polyimide precursor is prepared by dissolving a diamine and acidFor example, suitable solvents can include polar aprotic solvents. In some embodiments, diamines and acid At least one of the dianhydrides can contain an aromatic group.

[0024] In exemplary embodiments, the porous carbon sulfur composite can be a monolith. For example, the porous carbon sulfur composite can be a free-standing structure. The porous carbon sulfur composite can be fabricated on a substrate. In some embodiments, the porous carbon sulfur composite is reinforced with a non-woven material, e.g., a woven material. In some embodiments, the porous carbon sulfur composite can be pulverized to form a powder.

[0025] In an exemplary embodiment, the polyimide wet gel composite may be dried using subcritical and / or supercritical carbon dioxide to form a porous polyimide. In some embodiments, the composite may include an aerogel.

[0026] In an exemplary embodiment, the maximum pyrolysis temperature is about 750° C. to about 1600° C. In some embodiments, the porous carbon-sulfur composite is graphitized to about 3000° C. In some embodiments, the porous polyimide is preferably compressed uniaxially to increase density. For example, the porous polyimide can be compressed to a strain of about 95%. The porous carbon-sulfur composite can have a tunable density up to about 1.5 g / cc based on the amount of compression.

[0027] In exemplary embodiments, sulfur can be incorporated onto or into the continuous porous carbon by melt infusion. In some embodiments, sulfur is incorporated onto or into the continuous porous carbon by surface treating the continuous porous carbon with chemical functional groups that have an affinity for sulfur and polysulfides. [Brief description of the drawings]

[0028] For a fuller understanding of the present invention, reference should be made to the following detailed description taken in conjunction with the accompanying drawings, in which:

[0029] [Figure 1] 1 is a flow diagram illustrating the formation of sulfur-doped carbon aerogel for use in energy storage applications, such as lithium-sulfur batteries. [Figure 2A] FIG. 2 is a schematic diagram of a carbon aerogel, optionally disposed on a substrate. [Figure 2B] FIG. 1 is a schematic diagram of a carbon aerogel randomly disposed on a substrate, with electrochemically active species (e.g., elemental sulfur) forming a conformal coating on the carbon surface. [Figure 2C] FIG. 1 is a schematic diagram of a carbon aerogel optionally disposed on a substrate, with electrochemically active species (e.g., elemental sulfur) formed as nanoparticles within and bonded to the aerogel network. [Figure 3A] 1 is a SEM image of a sulfur-doped carbon material according to embodiments disclosed herein. [Figure 3B] 1 is a SEM image of a sulfur-doped carbon material according to embodiments disclosed herein. [Figure 4A] 13 shows the first cycle half-cell capacity at 0.1 C of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made with a target density of 0.05 g / cc. [Figure 4B] FIG. 1 shows the first cycle half-cell capacity at 1 C of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made with a target density of 0.05 g / cc. [Figure 5A] 1 shows the first cycle half-cell capacity at 0.1 C of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made with a target density of 0.125 g / cc. [Figure 5B] FIG. 1 shows the first cycle half-cell capacity at 1 C of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made with a target density of 0.125 g / cc. [Figure 6]13 shows the half-cell cycling performance of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made at a target density of 0.05 g / cc. [Figure 7] 13 shows the half-cell cycling performance of electrodes fabricated using sulfur-doped carbon material made from polyimide gel made at a target density of 0.125 g / cc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] In the following detailed description of the invention, reference is made to the accompanying drawings, which form a part hereof, and in which is shown by way of illustration specific embodiments in which the invention may be practiced It is to be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present invention.

[0031] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is used generally in its sense including "and / or" unless the context clearly dictates otherwise.

[0032] As used herein, "about" means approximately or approximately, and in the context of a stated numerical value or range, means ±15% of the numerical value. In embodiments, the term "about" can include conventional rounding to significant digits of the numerical value. Additionally, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'."

[0033] Within the context of this disclosure, the term "aerogel" or "aerogel material" refers to a gel that includes a skeleton of an interconnected structure with a corresponding network of interconnected pores embedded within the skeleton and that contains a gas, such as air, as a dispersed pore medium: the following physical and structural properties (as determined by nitrogen porosimetry testing) are attributed to aerogels: (a) an average pore size in the range of about 2 nm to about 100 nm; (b) a porosity of at least 80% or greater; and (c) a porosity of about 20 nm to about 100 nm. 2 / g or greater surface area. It can be appreciated that the inclusion of additives such as reinforcing materials or electrochemically active species can reduce the porosity of the resulting aerogel composite. Densification can also reduce the porosity of the resulting aerogel composite. This will become more clear as this specification continues.

[0034] Thus, the aerogel materials of the present disclosure include any aerogel or other open-cell compound that meets the defining elements set forth in the previous paragraph, including compounds that can be classified as xerogels, cryogels, ambigels, microporous materials, etc.

[0035] In the context of this disclosure, the term "skeleton" or "skeletal structure" refers to the network of interconnected oligomeric, polymeric, or colloidal particles that form the solid structure of a gel or aerogel. The polymers or particles that make up the scaffold structure typically have diameters of about 100 angstroms. However, the scaffold structure of this disclosure can also include a network of interconnected oligomeric, polymeric, or colloidal particles of all diameter sizes that form the solid structure within a gel or aerogel.

[0036] Within the context of this disclosure, the term "aerogel composition" refers to any composite that includes an aerogel material as a component of the composite. Examples of aerogel compositions include: Fiberaerogel composites containing added elements such as opacifiers and electrochemically active species; aerogel-foam composites; aerogel-polymer composites; and composites that incorporate aerogel particulates, particles, granules, beads or powder into solid or semi-solid materials such as binders, resins, cements, foams, polymers or similar solid materials.

[0037] Within the context of this disclosure, the term "reinforced aerogel composition" refers to an aerogel composition that includes a reinforcing phase within the aerogel material, where the aerogel composition is not part of the aerogel skeleton or can be modified to be covalently bonded to the aerogel skeleton. The reinforcing phase can be any material that provides the aerogel material with increased flexibility, elasticity, conformability, or structural stability. Examples of well-known reinforcing materials include open cell foam reinforcement, closed cell foam reinforcement, open cell membranes, honeycomb reinforcement, polymeric reinforcement, and discrete reinforcement. Fiber Fibers, woven materials, nonwoven materials, battings, webs, mats, and felts. Fiber Examples of reinforcing phases include, but are not limited to, fiber reinforcements. Additionally, the reinforcements may be combined with one or more of the other reinforcements and may be oriented continuously throughout the composition or in a limited preferred portion. In other embodiments, no reinforcing phase may be used at all if the aerogel material and / or aerogel framework is structurally stable by itself (i.e., self-supporting). This self-supporting nature of certain carbon aerogels will become more apparent as this specification continues.

[0038] Within the context of this disclosure, the term "wet gel" refers to a gel in which the mobile interstitial phase within a network of interconnected pores is composed primarily of a liquid phase, such as a conventional solvent, a liquefied gas, such as liquid carbon dioxide, or a combination thereof. Aerogels typically require the initial generation of a wet gel, followed by processing and extraction to replace the mobile interstitial liquid phase in the gel with air or another gas. Examples of wet gels include, but are not limited to, alcogels, hydrogels, ketogels, carbonogels, and any other wet gels known to those of skill in the art.

[0039] In the context of this disclosure, the term "additive" or "additive element" refers to a material that can be added to a composition before, during, or after the production of the composition. Additives can be added, for example, to modify or improve a desirable property in an aerogel composition, or to counteract or mitigate an undesirable property in an aerogel composition. Additives are typically added to an aerogel composition before or during gelation. Additives can also be added to an aerogel composition by atomic layer deposition or chemical vapor deposition (CVD). A particular example of an additive is an electrochemically active species, such as elemental sulfur.

[0040] In the context of this disclosure, the term "free-standing" refers to an aerogel material or composition that can be flexible and / or elastic, based primarily on the physical properties of the aerogel. Free-standing aerogel materials or compositions of the present disclosure can be distinguished from other aerogel materials, such as coatings, that rely on an underlying substrate or reinforcing material to provide the material with flexibility and / or elasticity.

[0041] In the context of this disclosure, the term "density" refers to a measure of the mass per unit volume of an aerogel material or composition. The term "density" generally refers to the true density of an aerogel material and the bulk density of an aerogel composition. Density is typically measured in kg / m 3or g / cc. The density of an aerogel material or composition can be determined by methods known in the art, including, but not limited to, Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, Pa.); Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTM C167, ASTM International, West Conshohocken, Pa.); or Determination of the apparent density of preformed pipe insulation (ISO 18098, International Organization for Standardization, Switzerland). Within the context of this disclosure, unless otherwise specified, density measurements are taken according to ASTM C 167. Preferably, the aerogel material or composition of the present disclosure has a density of 1.50 g / cc or less, 1.40 g / cc or less, 1.30 g / cc or less, 1.20 g / cc or less, 1.10 g / cc or less, 1.00 g / cc or less, 0.90 g / cc or less, 0.80 g / cc or less, 0.70 g / cc or less, 0.60 g / cc or less, 0.50 g / cc or less, 0.40 g / cc or less, 0.30 g / cc or less, 0.20 g / cc or less, 0.10 g / cc or less, or a range between any two of these values.

[0042] The manufacture of aerogels according to certain embodiments generally involves the following steps: i) forming a solution containing gel precursors; ii) forming a gel from the solution; and iii) extracting the solvent from the gel material to obtain a dry aerogel material. This process is described in more detail below, particularly in the context of forming organic aerogels such as polyimide aerogels. However, the specific examples and illustrations provided herein are not intended to limit the present disclosure to any particular type of aerogel and / or method of preparation. The present disclosure can include any aerogel formed by any relevant method of preparation known to one of skill in the art.

[0043] An exemplary solution for producing silica aerogel is formed by combining at least one gelling precursor with a solvent. Suitable solvents for use in forming the solution include lower alcohols having 1-6, preferably 2-4 carbon atoms, although other solvents may be used as known to those skilled in the art. Examples of useful solvents include, but are not limited to, methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, dichloromethane, tetrahydrofuran, and the like. Multiple solvents may also be combined to achieve a desired level of dispersion or to optimize the properties of the gel material. Thus, the selection of an optimal solvent for the polymerization and gel formation process depends on the particular precursors, fillers, and additives to be incorporated into the solution, as well as the target processing conditions for gelation and liquid phase extraction, and the desired properties of the final aerogel material.

[0044] An exemplary solution for producing polyimide aerogels is a mixture of at least one diamine and at least one amine in a common polar aprotic solvent. acidIt is formed by combining dianhydrides. Further details regarding the formation of polyimide gels / aerogels can be found in U.S. Pat. Nos. 7,074,880 and 7,071,287 to Rhine et al.; U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al., Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306(2011), Mrsf10-1306-bb03-01. doi:10.1557 / opl.2011.90; Chidambareswarapattar et al., One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons,J.Mater.Chem.,2010,20,9666-9678;Guo et al.,Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane,ACS Appl.Mater.Interfaces 2011,3,546-552;Nguyen et al.,Development of High Temperature,Flexible Polyimide Aerogels,American Chemical Society,proceedings published 2011;Meador et al.,Mechanically Strong,Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine,ACS Appl.Mater.Interfaces, 2012, 4(2), pp 536-544; Meador et al., Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels, ACS Appl. Mater. Interfaces 2015, 7, 1240-1249; Pei et al., Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383, each of which is incorporated herein by reference in its entirety. Triamines, tetraamines, pentamines, hexamines, and the like can also be used in place of or in addition to diamines or combinations thereof to optimize the properties of the gel material. acid Instead of or in addition to the dianhydrides or combinations thereof, acid trianhydride, acid tetraanhydride, acid pentahydride, acid Hexanhydrides can also be used. Dehydrating agents and catalysts can be incorporated into the solution to initiate and drive the imidization.

[0045] The solution may contain additional co-gelling precursors, as well as filler materials and other additives. The filler materials and other additives may be dispensed into the solution at any time prior to or during the formation of the gel. The filler materials and other additives may also be incorporated into the gel material after gelling by various techniques known to those skilled in the art. Preferably, the solution containing the gelling precursors, solvent, catalyst, water, filler materials, and other additives is a homogenous solution capable of forming an effective gel under appropriate conditions.

[0046] Once the solution is formed and optimized, the gel-forming components in the solution can be transferred to a gel material. The process of transferring the gel-forming components to a gel material includes an initial gel formation step, where the gel solidifies to the gel point of the gel material. The gel point of the gel material can be considered as the point at which the gelling solution exhibits resistance to flow and / or forms a substantially continuous polymer backbone throughout its volume. Various gel formation techniques are known to those skilled in the art. Examples include, but are not limited to, maintaining the mixture in a quiescent state for a sufficient period of time; adjusting the concentration of the catalyst; adjusting the temperature of the solution; directing a form of energy to the mixture (ultraviolet, visible, infrared, microwave, ultrasonic, particle radiation, electromagnetic); or a combination thereof.

[0047] The process of transferring gel-forming components into the gel material can also include an aging step (also called curing) prior to liquid-phase extraction. Aging the gel material after reaching the gel point can further strengthen the gel skeleton by increasing the number of crosslinks in the network. The duration of gel aging can be adjusted to control various properties within the resulting aerogel material. This aging procedure can be useful to prevent potential volume loss and shrinkage during liquid-phase extraction. Aging can include maintaining the gel in a quiescent state for an extended period of time (prior to extraction); maintaining the gel at an elevated temperature; adding a crosslinking-promoting compound; or any combination thereof. The preferred temperature for aging is usually from about 10°C to about 200°C. Aging of the gel material typically continues until liquid-phase extraction of the wet gel material.

[0048] The time for transitioning the gel-forming material into a gel material includes both the duration of initial gel formation (from the onset of gelation to the gel point) and the duration of any subsequent hardening and aging of the gel material prior to liquid phase extraction (from the gel point to the onset of liquid phase extraction). The total time for transitioning the gel-forming material into a gel material is typically between about 1 minute and several days, preferably about 30 hours or less, about 24 hours or less, about 15 hours or less, about 10 hours or less, about 6 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, or about 15 minutes or less.

[0049] The resulting gel material can be washed in a suitable secondary solvent to displace the primary reaction solvent present in the wet gel. Such secondary solvents can be linear monohydric alcohols having one or more aliphatic carbon atoms, dihydric alcohols having two or more carbon atoms, branched alcohols, cyclic alcohols, alicyclic alcohols, aromatic alcohols, polyhydric alcohols, ethers, ketones, cyclic ethers, or derivatives thereof.

[0050] Once the gel material has been formed and processed, extraction methods, including processing and extraction techniques, can then be used to at least partially extract the liquid phase of the gel from the wet gel to form the aerogel material. Liquid phase extraction plays an important role in manipulating the properties of the aerogel, such as porosity and density, and related properties, such as thermal conductivity, among other factors. In general, aerogels are obtained when the liquid phase is extracted from the gel in a manner that causes low shrinkage in the porous network and skeleton of the wet gel.

[0051] Aerogels are generally formed by removing a liquid mobile phase from a gel material at temperatures and pressures near or above the critical point of the liquid mobile phase. Once the critical point is reached or surpassed (supercritical) (i.e., the pressure and temperature of the system are at or above the critical pressure and critical temperature, respectively), a new supercritical phase appears in the fluid that is distinct from the liquid or gas phase. The solvent can then be removed without introducing liquid-vapor interfaces, capillary pressures, or any of the associated mass transfer limitations typically associated with liquid-vapor boundaries. In addition, the supercritical phase is generally more miscible with organic solvents and therefore has better extraction capabilities. Co-solvents and solvent exchanges are also commonly used to optimize supercritical fluid drying processes.

[0052] If evaporation or extraction occurs below the supercritical point, capillary forces resulting from evaporation of the liquid can cause shrinkage and collapse of pores within the gel material. By maintaining the mobile phase near or above the critical pressure and temperature during the solvent extraction process, the adverse effects of such capillary forces are reduced. In certain embodiments of the present disclosure, the use of near-critical conditions just below the critical point of the solvent system allows for the production of aerogel materials or compositions with sufficiently low shrinkage to produce a commercially viable end product.

[0053] Several additional aerogel extraction techniques are known in the art, including a range of different approaches in using supercritical fluids in drying aerogels, as well as ambient drying techniques. For example, Kistler (J. Phys. Chem. (1932) 36:52-64) describes a simple supercritical extraction process in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing the evaporative capillary forces and maintaining the structural integrity of the gel network. U.S. Pat. No. 4,610,863 describes an extraction process in which the gel solvent is exchanged with liquid carbon dioxide, followed by extraction with the carbon dioxide in a supercritical state. U.S. Pat. No. 6,670,402 teaches the extraction of the liquid phase from the gel via rapid solvent exchange by injecting supercritical (rather than liquid) carbon dioxide into an extractor that is preheated and prepressurized substantially above the supercritical state, thereby producing an aerogel. US Patent No. 5,962,539 describes a method of obtaining an aerogel from a polymeric material in the form of a sol-gel in an organic solvent by exchanging the organic solvent with a fluid having a critical temperature below the polymer decomposition temperature and supercritical extraction of the fluid / sol-gel. US Patent No. 6,315,971 discloses a method of producing a gel composition comprising drying a wet gel containing gel solids and a desiccant to remove the desiccant under drying conditions sufficient to reduce shrinkage of the gel during drying. US Patent No. 5,420,168 describes a method by which resorcinol / formaldehyde aerogels can be produced using a simple air-drying procedure. US Patent No. 5,565,142 describes a drying technique that modifies the gel surface to be stronger and more hydrophobic so that the gel skeleton and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting liquid phases from aerogel materials can be found in US Patents 5,275,796 and 5,395,805.

[0054] One preferred embodiment of extracting the liquid phase from the wet gel involves using supercritical conditions of carbon dioxide, for example, by first substantially exchanging the primary solvent present in the pore network of the gel with liquid carbon dioxide; and then heating the wet gel (usually in an autoclave) above the critical temperature of carbon dioxide (about 31.06° C.) and increasing the pressure of the system to a pressure higher than the critical pressure of carbon dioxide (about 1070 psig). The pressure surrounding the gel material can be slightly fluctuated to facilitate the removal of the supercritical carbon dioxide fluid from the gel. Carbon dioxide can be recirculated through the extraction system to facilitate the continuous removal of the primary solvent from the wet gel. Finally, the temperature and pressure are slowly returned to ambient conditions to produce a dry aerogel material. Carbon dioxide can also be pretreated to a supercritical state before being injected into the extraction chamber. In other embodiments, the extraction can be performed by any suitable mechanism, such as by varying the pressure, timing, and solvent described above.

[0055] In certain embodiments of the present disclosure, the dried polyimide aerogel composition may be subjected to one or more heat treatments for durations of 3 hours or more, 10 seconds to 3 hours, 10 seconds to 2 hours, 10 seconds to 1 hour, 10 seconds to 45 minutes, 10 seconds to 30 minutes, 10 seconds to 15 minutes, 10 seconds to 5 minutes, 10 seconds to 1 minute, 1 minute to 3 hours, 1 minute to 1 hour, 1 minute to 45 minutes, 1 minute to 30 minutes, 1 minute to 15 minutes, 1 minute to 5 minutes, 10 minutes to 3 hours, 10 minutes to 1 hour, 10 minutes to 45 minutes, 10 minutes to 30 minutes, 10 minutes to 15 minutes, 30 minutes to 3 hours, 30 minutes to 1 hour, 30 minutes to 45 minutes, 45 minutes to 3 hours, 45 minutes to 90 minutes, 45 minutes to 60 minutes, 1 hour to 3 hours, 1 hour to 2 hours, 1 hour to 90 minutes.

[0056] In certain embodiments, the invention involves the formation and use of nanoporous carbon-based scaffolds or structures, such as carbon aerogels, as electrode materials in energy storage devices, e.g., as the primary cathode material in LSBs. The pores of the nanoporous scaffold are designed, organized, and structured to accommodate sulfur, iron phosphate, or other suitable species. Alternatively, the pores of the nanoporous scaffold may be filled with sulfides, hydrides, any suitable polymer, or other additives where it is beneficial to contact the additive with the conductive material (i.e., the scaffold / aerogel) to provide a more effective electrode.

[0057] To further expand on the exemplary applications within the LSB, when carbon aerogel materials are utilized as the primary cathode material, as in certain embodiments of the present invention, the nanoporous structure of the aerogel has a narrow pore size distribution, with high electrical conductivity, high mechanical strength, and a morphology and sufficient pore volume (at final density) to accommodate a high weight percent of elemental sulfur and its expansion. Structurally, certain embodiments of the present invention have strut sizes that produce the narrow pore size distribution and high pore volume described above, among other properties. Fibril morphology and enhanced binding.

[0058] As discussed further below, the surface of the carbon aerogel may be modified by chemical, physical, or mechanical methods to enhance the performance of the sulfur and polysulfides contained within the pores of the carbon aerogel.

[0059] In additional or alternative embodiments, the carbon aerogel itself acts as a current collector due to its electrical conductivity and mechanical strength, and thus in preferred embodiments, no separate current collector is required on the cathode side (if the cathode is formed of carbon aerogel). Of note, in conventional LSBs, aluminum foil is bonded to the cathode as its current collector. However, depending on the carbon aerogel application, removing one or both of these components would create additional space for more electrode material, further increasing the capacity of the cell / individual electrodes and the overall energy density of the packaged battery system. However, in certain embodiments, the existing current collector may be integrated with the cathode material of various other embodiments to enhance the current collection capability or capacity of the aluminum foil.

[0060] In certain embodiments, the nanoporous carbon-based scaffold or structure, particularly carbon aerogel, can be used as a conductive network or current collector on the cathode side of the energy storage device. The fully interconnected carbon aerogel network is filled with electrochemically active species, which are in direct contact or physically connected to the carbon network. The loading of the electrochemically active species is adjusted to the pore volume and porosity for high stable capacity and improved safety of the energy storage device. When utilized on the cathode side, the electrochemically active species can include, for example, sulfur, iron phosphate, or other functionally suitable species. In yet another embodiment, the cathode can include a nanoporous carbon-based scaffold or structure, particularly carbon aerogel.

[0061] In the context of this disclosure, "current collector noneThe term "current collector" refers to the absence of a separate current collector directly connected to the electrode. As discussed above, in conventional LSBs, an aluminum foil is typically bonded to the cathode as its current collector. According to embodiments of the present invention, an electrode formed from a nanoporous carbon-based scaffold or structure (e.g., carbon aerogel) can be a freestanding structure, as the scaffold or structure itself acts as a current collector due to its high electrical conductivity, or it can be a current collector that is otherwise not required. none In electrochemical cells, the continuous porous carbon can function as a current collector by embedding a solid, mesh, or woven tab during the solution process that produces the continuous porous carbon, or by soldering, welding, or metal depositing a lead onto a portion of the porous carbon surface. None The electrodes can be connected to form a circuit. Other mechanisms for contacting the carbon to the rest of the system are also contemplated herein. In an alternative embodiment, the nanoporous carbon-based scaffold or structure, specifically the carbon aerogel, may be placed on or otherwise in communication with a dedicated current collecting substrate (e.g., copper foil, aluminum foil, etc.). In this scenario, the carbon aerogel may be attached to a solid current collector using a conductive adhesive and various amounts of pressure may be applied.

[0062] It is further contemplated herein that the nanoporous carbon-based scaffold or structure, particularly carbon aerogel, can be in the form of a monolithic structure or in powder form. Being essentially monolithic, the carbon aerogel eliminates the need for any binder. In other words, the cathode does not require a binder. none As used herein, the term "monolithic" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material or composition is in the form of a single, continuous, interconnected aerogel nanostructure. Monolithic aerogel materials include aerogel materials that are initially formed to have an integrally interconnected gel or aerogel nanostructure, but may subsequently be cracked, broken, or segmented into non-integral aerogel nanostructures. Monolithic aerogels are free-standing or reinforced ( FiberIn comparison, using LSB as an example, sulfur incorporated into a monolithic aerogel can be more effectively utilized relative to its theoretical capacity compared to the same amount of sulfur incorporated into a slurry using conventional processes.

[0063] Monolithic aerogel materials are distinguished from granular aerogel materials. The term "granular aerogel materials" refers to aerogel materials in which the majority of the aerogel contained in the aerogel material (by weight) is in the form of particulates, particles, granules, beads or powders that can be combined together (i.e., via a binder, such as a polymeric binder) or compressed together, but lack the interconnected nanostructure of aerogel between the individual particles. Collectively, aerogel materials in this form are referred to as having a powder or particle form (as opposed to a monolithic form). It should be noted that, despite the individual particles of the powder having a single structure, the individual particles are not considered monoliths herein. Integration of aerogel powders into electrochemical cells typically involves making a paste or slurry from the powder, casting on a substrate and drying, and may optionally include calendering.

[0064] In the context of this disclosure, "binding agent" none The term "binder-free" (or derivatives thereof) refers to a material that is substantially free of binders or adhesives to hold the material together. For example, a monolithic nanoporous carbon material does not contain a binder because its skeleton is formed as an integral, continuous, interconnected structure. Binder noneThe advantages of being binder-free include avoiding any adverse effects of binders on electrical conductivity, pore volume, etc. Aerogel powders or particles, on the other hand, require a binder to hold them together to form a larger functional material. Such larger materials are not considered to be monoliths herein. Furthermore, the term "binder-free" does not exclude the total use of binders. For example, a monolithic aerogel according to the present invention may be secured to another monolithic aerogel or non-aerogel material by placing a binder or adhesive on a major surface of the aerogel material. In this way, a binder is used to create a laminated composite, but the binder does not function to maintain the stability of the monolithic aerogel framework itself.

[0065] Additionally, the monolithic polymer aerogel material or composition of the present disclosure may be compressed at strains up to 95% without significant destruction or fracturing of the aerogel skeleton, while densifying the aerogel and reducing porosity to a minimum. In certain embodiments, the compressed polymer aerogel material or composition is subsequently carbonized using various methods described herein to form a nanoporous carbon material. It can be understood that the amount of compression affects the thickness of the resulting carbon material, which in turn affects the volume, as will become more clear as the present specification continues. The examples described below show the various thicknesses formed and contemplated by the present invention, which thickness is adjustable based on compression. Thus, the thickness of the composite (typically compressed) can be about 10-1000 μm, or any narrower range therein, based on the benefits desired for the final composite. The present invention also contemplates powder or particulate forms of carbon aerogel where a binder is required and particle size is optimized. Particle size ranges can be about 5-50 μm.

[0066] Nanoporous carbons, such as carbon aerogels according to the present invention, can be formed from any suitable organic precursor material. Examples of such materials include, but are not limited to, RF, PF, PI, polyamides, polyacrylates, polymethylmethacrylates, acrylate oligomers, polyoxyalkylenes, polyurethanes, polyphenols, polybutadienes, trialkoxysilyl-terminated polydimethylsiloxanes, polystyrenes, polyacrylonitriles, polyfurfurals, melamine-formaldehyde, cresol formaldehyde, phenol-furfurals, polyethers, polyols, polyisocyanates, polyhydroxybenz, polyvinyl alcohol dialdehyde, polycyanurates, polyacrylamides, various epoxies, agar, agarose, chitosan, and combinations and derivatives thereof. Any precursor of these materials can be used to make and use the resulting material. In an exemplary embodiment, the carbon aerogels are formed from pyrolyzed / carbonized polyimide-based aerogels, i.e., polymerization of polyimides. Even more specifically, polyimide-based aerogels can be produced using one or more of the methodologies described in U.S. Pat. Nos. 7,071,287 and 7,074,880 to Rhine et al., for example, by imidization of poly(amide) acids and drying the resulting gel using supercritical fluids. Other suitable methods of making polyimide aerogels (and carbon aerogels derived therefrom) are also contemplated herein, and include, for example, U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01. doi:10.1557 / opl.2011.90;Chidambareswarapattar et al.,One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons,J.Mater.Chem.,2010,20,9666-9678;Guo et al.,Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane,ACS Appl.Mater.Interfaces 2011,3,546-552;Nguyen et al.,Development of High Temperature,Flexible Polyimide Aerogels,American Chemical Society,proceedings published 2011;Meador et al.,Mechanically Strong,Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine,ACS Appl.Mater.Interfaces,2012,4(2),pp 536-544;Meador et al.,Polyimide Aerogels with Amide Cross-Links:A Low Cost Alternative for Mechanically Strong Polymer Aerogels,ACS Appl.Mater.Interfaces 2015,7,1240-1249;Pei et al., Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383. The resulting polyimide aerogel is then pyrolyzed to form a polyimide-derived carbon aerogel.

[0067] Carbon aerogels according to exemplary embodiments of the present disclosure, such as polyimide-derived carbon aerogels, can have a residual nitrogen content of at least about 4% by weight. For example, carbon aerogels according to embodiments disclosed herein can have a residual nitrogen content of at least about 0.1%, at least about 0.5%, at least about 1%, at least about 2%, at least about 3%, at least about 4%, at least about 5%, at least about 6%, at least about 7%, at least about 8%, at least about 9%, at least about 10%, or a range between any two of these values.

[0068] In certain embodiments of the present disclosure, the dry polymer aerogel composition can be subjected to a processing temperature of 200° C. or more, 400° C. or more, 600° C. or more, 800° C. or more, 1000° C. or more, 1200° C. or more, 1400° C. or more, 1600° C. or more, 1800° C. or more, 2000° C. or more, 2200° C. or more, 2400° C. or more, 2600° C. or more, 2800° C. or more, or a range between any two of these values, for carbonization of the organic (e.g., polyimide) aerogel. In exemplary embodiments, the dry polymer aerogel composition can be subjected to a processing temperature ranging from about 1000° C. to about 1100° C., e.g., about 1050° C. Without being bound by theory, it is contemplated herein that the electrical conductivity of the aerogel composition increases with carbonization temperature.

[0069] Within the context of this disclosure, the term "electrical conductivity" refers to a measurement of a material's ability to conduct electric current or otherwise allow electrons to flow through or within it. Electrical conductivity is specifically measured as the conductivity / susceptance / admittance of a material per unit size of the material. It is typically recorded as S / m (Siemens / meter) or S / cm (Siemens / centimeter). The electrical conductivity or resistivity of a material can be determined by methods known in the art, including, for example, but not limited to, series 4-point resistivity (using the dual configuration test method of ASTM F84-99). Within the context of this disclosure, unless otherwise stated, electrical conductivity measurements are obtained according to the ASTM F84-resistivity (R) measurement, which is obtained by measuring the voltage (V) divided by the current (I). In certain embodiments, the aerogel material or composition of the present disclosure has a conductivity of about 1 S / cm or greater, about 5 S / cm or greater, about 10 S / cm or greater, 20 S / cm or greater, 30 S / cm or greater, 40 S / cm or greater, 50 S / cm or greater, 60 S / cm or greater, 70 S / cm or greater, 80 S / cm or greater, or a range between any two of these values.

[0070] In the context of this disclosure, the term "electrochemically active species" refers to an additive capable of accepting and releasing ions in an energy storage device. Using LSB as an example, the electrochemically active species in the cathode accepts lithium ions during discharge (thus undergoing conversion to lithium sulfide species) and releases lithium ions during charging. The electrochemically active species can be stabilized in the cathode by having a direct / physical bond with the nanoporous carbon. In certain embodiments, the nanoporous carbon network forms an interconnected structure around the electrochemically active species. The electrochemically active species is bonded to the nanoporous carbon at multiple points. An example of an electrochemically active species is sulfur, which expands when converted to lithium sulfide. However, because sulfur has multiple connection points with the nanoporous carbon (aerogel), the sulfur can be retained within the pores and remain active. The amount of sulfur incorporated into the nanoporous carbon material can be enhanced compared to conventional cathodes with LSB. In certain embodiments, the aerogel material or composition of the present disclosure has a sulfur content between about 5% by weight of the cathode and about 90% by weight of the cathode, or any range between these two values.

[0071] In the context of this disclosure, the terms "compressive strength", "flexural strength", and "tensile strength" refer to the resistance of a material to break or fracture under compressive, bending or flexing, and tensile or pulling forces, respectively. These strengths are specifically measured as the amount of load / force per unit area that resists the load / force. This is typically recorded as pounds per square inch (psi), megapascals (MPa), or gigapascals (GPa). Among other things, the compressive, flexural, and tensile strengths of a material collectively contribute to the structural integrity of the material, which is beneficial in LSB. With particular reference to Young's modulus, which is an indicator of mechanical strength, this modulus can be determined by methods known in the art, including, for example, but not limited to, Standard Test Practice for Instrumented Indentation Testing (ASTM E2546, ASTM International, West Conshocken, PA); or Standardized Nanoindentation (ISO 14577, International Organization for Standardization, Switzerland). Within the context of this disclosure, Young's modulus measurements are taken in accordance with ASTM E2546 and ISO 14577, unless otherwise specified. In certain embodiments, the aerogel materials or compositions of the present disclosure have a Young's modulus of about 0.2 GPa or more, 0.4 GPa or more, 0.6 GPa or more, 1 GPa or more, 2 GPa or more, 4 GPa or more, 6 GPa or more, 8 GPa or more, or in the range between any two of these values.

[0072] Within the context of this disclosure, the term "pore size distribution" refers to the statistical distribution or relative amount of each pore size within a sample volume of a porous material. A narrower pore size distribution refers to a relatively large percentage of pores in a narrow range of pore sizes, thus optimizing the amount of pores that can surround electrochemically active species and maximizing the use of the pore volume. Conversely, a wider pore size distribution refers to a relatively small percentage of pores in a narrow range of pore sizes. Thus, the pore size distribution is typically measured as a function of pore volume and recorded as a size in units of full width at half maximum of the main peak of a pore size distribution chart. The pore size distribution of a porous material can be determined by methods known in the art, including, for example, but not limited to, surface area and porosity analyzers by nitrogen adsorption / desorption, which can calculate the pore size distribution. Within the context of this disclosure, measurements of the pore size distribution are obtained according to this method unless otherwise specified. In certain embodiments, the aerogel material or composition of the present disclosure has a relatively narrow pore size distribution (full width at half maximum) of about 50 nm or less, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 15 nm or less, 10 nm or less, 5 nm or less, or a range between any two of these values.

[0073] In the context of the present disclosure, the term "pore volume" refers to the total volume of pores within a sample of a porous material. Pore volume is specifically measured as the volume of void space within a porous material, which void space may be measurable and / or accessible to another material, e.g., an electrochemically active species such as sulfur. This is usually measured in cubic centimeters per gram (cm 3The pore volume of a porous material can be determined by methods known in the art, including, for example, but not limited to, surface area and porosity analyzers by nitrogen adsorption / desorption, which can calculate the volume of the pore size. Within the context of the present disclosure, measurements of pore volume are taken according to this method unless otherwise indicated. In certain embodiments, the aerogel material or composition of the present disclosure (without incorporating an electrochemically active species, e.g., sulfur) has a relatively large pore volume of about 1 cc / g or more, 1.5 cc / g or more, 2 cc / g or more, 2.5 cc / g or more, 3 cc / g or more, 3.5 cc / g or more, 4 cc / g or more, or a range between any two of these values. In other embodiments, the aerogel materials or compositions of the present disclosure (incorporating an electrochemically active species, e.g., sulfur) have a pore volume of about 0.10 cc / g or more, 0.3 cc / g or more, 0.6 cc / g or more, 0.9 cc / g or more, 1.2 cc / g or more, 1.5 cc / g or more, 1.8 cc / g or more, 2.1 cc / g or more, 2.4 cc / g or more, 2.7 cc / g or more, 3.0 cc / g or more, 3.3 cc / g or more, 3.6 cc / g or more, or a range between any two of these values.

[0074] Within the context of the present disclosure, the term "porosity" refers to the volume fraction of the pores that does not contain another material (e.g., an electrochemically active species such as sulfur) bound to the walls of the pores. For purposes of clarity and illustration, it is noted that in certain implementations of sulfur-doped carbon aerogels as the primary cathode material in the LSB, porosity refers to the void space after including elemental sulfur. Porosity may be determined by methods known in the art, including, for example, but not limited to, the ratio of the volume of the pores of the aerogel material to its bulk density. Within the context of the present disclosure, porosity measurements are obtained according to this method unless otherwise indicated. In certain embodiments, the aerogel materials or compositions of the present disclosure have a porosity of about 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or a range between any two of these values.

[0075] It should be noted that pore volume and porosity are different measures for the same property of the pore structure, namely the "empty space" within the pore structure. For example, when sulfur is used as an electrochemically active species enclosed within the pores of a nanoporous carbon material, the pore volume and porosity refer to the "empty" space, i.e., the space not utilized by carbon or the electrochemically active species. As can be seen, densification of the pre-carbonized nanoporous material, for example by compression, can affect the pore volume and porosity, among other properties.

[0076] In the context of this disclosure, the term "pore size at the maximum peak from a distribution" refers to the value at a identifiable peak on a graph showing the distribution of pore sizes. The pore size at the maximum peak from a distribution is specifically measured as the pore size at which the largest percentage of pores are formed. This is typically recorded as any unit length of pore size, such as μm or nm. The pore size at the maximum peak from a distribution can be determined by methods known in the art, including, for example, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, which can calculate the distribution of pore sizes and determine the pore size at the maximum peak. In the context of this disclosure, the measurement of the pore size at the maximum peak from a distribution is obtained according to this method unless otherwise specified. In certain embodiments, the aerogel material or composition of the present disclosure has a pore size at the largest peak from a distribution of about 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 2 nm or less, or a range between any two of these values.

[0077] In the context of this disclosure, the term "strut width" means Fibril Forming aerogels with morphology: nanostruts, nanorods, nano Fiber, or refers to the average diameter of the nanofilaments. It is typically recorded as any unit length, e.g., μm or nm. Strut width can be determined by methods known in the art, including, for example, but not limited to, scanning electron microscope image analysis. Within the context of the present disclosure, strut width measurements are taken according to this method unless otherwise noted. In certain embodiments, the aerogel materials or compositions of the present disclosure have strut widths of about 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4 nm or less, 3 nm or less, 2 nm or less, or in the range between any two of these values. Smaller strut widths, such as strut widths in the range of about 2-5 nm, allow for a greater amount of struts to be present in the network and therefore in contact with the electrochemically active species, which in turn allows for more electrochemically active species to be present in the composite. This improves electrical conductivity and mechanical strength.

[0078] Within the context of the present disclosure, the term "fibrillar morphology" refers to a structural morphology of nanoporous carbon (e.g., aerogel) that includes struts, rods, fibers, or filaments. For example, in embodiments, the choice of solvent, such as dimethylacetamide (DMAC), can affect the production of such morphologies. Furthermore, in certain embodiments, where the carbon aerogel is derived from a polyimide, the crystalline polyimide results from a polyimide that forms a linear polymer. As will become clearer in the examples below, certain embodiments surprisingly provide a crystalline polyimide that forms a linear polymer as an interconnected polymer structure. Fibril It has been observed that the product morphology contains long linear structures, where long linear structures were expected based on the known behavior of polyimide precursors. In comparison, the product morphology of nanoporous carbon is instead similar to that of carbon aerogels. Fibril The form may be of a particulate nature or powder that persists in nature. As will become apparent as the present specification continues, particularly when the nanoporous carbon is implemented in certain applications, such as as a material for the cathode in an LSB, Fibril The morphology can provide certain advantages over the particle morphology, such as mechanical stability / strength and electrical conductivity. FibrilThe morphology can be found in nanoporous carbon in both monolithic and powder form. In other words, monolithic carbon is Fibril The aerogel powder / particles can have the following morphology: Fibril It should be noted that the nanoporous carbon material may have a morphology similar to that of the nanoporous carbon material described above. Furthermore, in certain embodiments, when the nanoporous carbon material contains an additive such as sulfur, the inherent fibrillar nanostructure of the carbon material is preserved and acts as bridges between the additive particles.

[0079] Within the context of this disclosure, the term "cycle life" refers to the number of complete charge / discharge cycles that a cathode or battery (e.g., LSB) can support before its capacity falls below about 80% of its original rated capacity. Cycle life can be influenced by a variety of factors that are not significantly affected over time, such as the mechanical strength of the underlying substrate (e.g., carbon aerogel), the connectivity of sulfur within the aerogel, dissolution of sulfur or polysulfides into the electrolyte within the aerogel network, and maintenance of aerogel interconnectivity. It is noted that it is a surprising aspect of certain embodiments of the present invention that these factors remain relatively unchanged over time. Cycle life can be determined by methods known in the art, such as, but not limited to, cycle testing, in which a battery cell is subjected to repeated charge / discharge cycles at a given current rate and operating voltage. Within the context of this disclosure, cycle life measurements are taken according to this method unless otherwise specified. In certain embodiments of the present disclosure, the energy storage device, e.g., a battery, or an electrode thereof, has a cycle life of about 25 cycles or more, 50 cycles or more, 75 cycles or more, 100 cycles or more, 200 cycles or more, 300 cycles or more, 500 cycles or more, 1000 cycles or more, or a range between any two of these values.

[0080] In the context of this disclosure, the term "capacity" refers to the amount of specific energy or charge that a battery can store. Capacity is specifically measured as the discharge current that a battery can deliver over time per unit mass. It is typically recorded as ampere-hours or milliampere-hours per gram of total electrode mass, Ah / g or mAh / g. The capacity of a battery (and particularly the cathode) can be determined by methods known in the art, including, but not limited to, applying a fixed constant current load to a fully charged cell until the cell voltage reaches the end of the discharge voltage value; the time to reach the end of the discharge voltage multiplied by the constant current is the discharge capacity; specific capacity and volumetric capacity can be determined by dividing the discharge capacity by the weight or volume of the electrode material. In the context of this disclosure, capacity measurements are taken according to this method unless otherwise specified. In certain embodiments, the aerogel material or composition of the present disclosure has a capacity of about 200 mAh / g or more, 300 mAh / g or more, 400 mAh / g or more, 500 mAh / g or more, 600 mAh / g or more, 700 mAh / g or more, 800 mAh / g or more, 900 mAh / g or more, 1000 mAh / g or more, 1100 mAh / g or more, 1200 mAh / g or more, 1300 mAh / g or more, 1400 mAh / g or more, 1500 mAh / g or more, 1600 mAh / g or more, 1700 mAh / g or more, or a range between any two of these values.

[0081] In a particular embodiment, the present invention is a PI-derived nanoporous carbon material (e.g., carbon aerogel) with a series of pores that surround, contain, or encapsulate elemental sulfur. The nanoporous carbon material serves as an ideal host for sulfur due to its optimal pore structure, functional pore morphology, and high mechanical integrity. The nanoporous carbon material (carbon aerogel) results in consistent behavior of sulfur and polysulfide species throughout the network characterized by a narrow pore size distribution. The carbon material itself is further characterized by high electrical conductivity that helps overcome a major drawback of conventional LSBs, namely the high resistivity of sulfur and polysulfide species. The above features of the present nanoporous carbon material, individually and in combination, confer certain advantages that increase the cycle life and cell life of the resulting LSB system or its cathode.

[0082] In an embodiment, the invention is a cathode of an LSB comprising a sulfur-doped polyimide-derived carbon aerogel, in which elemental sulfur is enclosed within the pores of the carbon aerogel (see Figures 2A-2C). As can be seen, the structure of the carbon aerogel pores can be tailored to have different properties (e.g., pore volume, pore size, pore size distribution, and surface area) based on the need (e.g., size or capacity of the electrode in the LSB). In another embodiment, the invention is an electrode of an LSB or electrochemical cell thereof comprising such a cathode. In the LSB, sulfur cathodes (such as those described herein as sulfur-doped nanoporous carbon materials or sulfur-doped carbon aerogels) are most commonly paired with lithium metal anodes to achieve balanced capacity. These sulfur cathodes can also be paired with non-lithium metal anodes that can achieve high capacity, including, for example, silicon-based, silicon-doped, or silicon-dominant anode materials. In yet a further embodiment, the invention is a device or system incorporating such an energy storage device.

[0083] In a particular embodiment, the present invention is a method for forming or producing a sulfur-doped continuous porous carbon composite, such as a carbon aerogel. acid Polyimide precursors, such as dianhydrides, are mixed in a suitable solvent (e.g., polar, aprotic solvent). An imidization gelling catalyst is then added to initiate the mixture for gelation. In an alternative embodiment, imidization can be accomplished by thermal imidization, where any suitable temperature and time range is contemplated (e.g., heating at about 100°C-200°C for about 20 minutes to about 8 hours, followed by heating at about 300°C-400°C for about 20 minutes to about 1 hour). The gelled mixture is then dried to obtain a continuous porous polyimide composite, where drying can be performed using subcritical and / or supercritical carbon dioxide. Optionally, the polyimide composite can be compressed to increase density, which is adjustable down to about 1.5 g / cc based on the amount of compression. In an exemplary embodiment, the polyimide composite can be compressed to greater than about 80% strain before pyrolyzing the composite. Whether or not compression is performed, the polyimide composite is pyrolyzed to produce a continuous porous carbon, where the carbon contains a porosity between about 5% and 99%. In certain embodiments, pyrolysis can be carried out at a maximum temperature of about 750°C to about 1600°C, for example about 1050°C, with optional graphitization at about 1600°C to about 3000°C.

[0084] After carbonization, sulfur is incorporated into the network of the porous carbon using any suitable method to form a sulfur-doped continuous porous carbon composite. An exemplary method of incorporating sulfur into the carbon network is by melt infusion. This incorporation can be controlled to achieve optimal sulfur weight loading and retained porosity. For example, the aerogel material or composition of the present disclosure can have a sulfur content of about 5 wt%, about 10 wt%, about 15 wt%, about 20 wt%, about 25 wt%, about 30 wt%, about 35 wt%, about 40 wt%, about 45 wt%, about 50 wt%, about 55 wt%, about 60 wt%, about 65 wt%, about 70 wt%, about 75 wt%, about 80 wt%, about 85 wt%, about 90 wt%, or a range between any two of these values. In an exemplary embodiment, the sulfur-doped nanoporous carbon material of the present disclosure can have a sulfur content in the range of about 60 wt% to 75 wt%, for example about 70 wt%. The aerogel material or composition of the present disclosure has a density of 10 mg / cm 2 Over 8mg / cm 2 More than 7mg / cm 2 More than 6mg / cm 2 More than 5mg / cm 2 More than 4mg / cm 2 More than 3mg / cm 2 More than 2.5mg / cm 2 More than 2mg / cm 2 More than 1.5mg / cm 2 More than 1mg / cm 2 In an exemplary embodiment, the sulfur-doped nanoporous carbon material of the present disclosure can have an areal mass loading of sulfur of about 1.5 mg / cm or more, or in a range between any two of these values. 2 ~about 2.5mg / cm 2 in the range of, for example, about 2 mg / cm 2 The sulfur may have an areal mass loading of 0.1 to 0.5 μm.

[0085] The incorporation of sulfur into the porous carbon network reduces the porosity of the sulfur-doped carbon composite from that of the undoped material. This results in smaller pore sizes in the sulfur-doped composite than those of the undoped material. In another example, or in combination with melt infusion, the native carbon network can be surface treated with chemical functional groups that have an affinity for sulfur and polysulfides to enhance containment within the network and help stabilize cycle life capacity. In yet another embodiment, additives can be included with the gel precursor (i.e., pregelation) to aid in the chemical or physical accommodation of the sulfur added after carbonization.

[0086] In certain embodiments, the carbon-sulfur composites may be monolithic or free-standing, may be fabricated on or off a substrate, or may be pulverized into a powder form. Additionally, the composites may be attached to non-woven or woven materials (e.g., Fiber The carbon-sulfur composites may be reinforced with or without additional additives (fibers, foams, etc.). Optionally, the carbon-sulfur composites may be selectively doped with nitrogen, either alone or in combination with other suitable additives, to inhibit polysulfide diffusion and thus preserve high cycle life.

[0087] In certain embodiments, the sulfur-doped nanoporous carbon material or composition of the present disclosure has a pore size at the maximum peak from the distribution of about 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 2 nm or less, or a range between any two of these values. Furthermore, it is contemplated herein that the pore size can be adjusted as needed. For example, the pore size can be adjusted to accommodate a sufficient amount of electrolyte for efficient battery operation when the sulfur-doped carbon material is incorporated into a battery. There are five primary ways to adjust the pore size taught herein. First, the amount of solids, specifically the polyimide precursor monomers (e.g., aromatic or aliphatic diamines and aromatic or aliphatic diamines), can be adjusted to accommodate a sufficient amount of electrolyte for efficient battery operation. acid The amount of dianhydride can adjust the pore size. Smaller pore sizes result from a higher amount of solids per unit volume of fluid, since there is less space available for the interconnections to be made closer together. Note that the strut width does not change measurably regardless of the amount of solids used. The amount of solids is related to the density of the network.

[0088] Another method of tailoring pore size is to use radiation (e.g., radio waves, microwaves, infrared, visible light, ultraviolet light, x-rays, gamma rays) on the composite in either the polyimide or carbon state. Radiation has an oxidizing effect, resulting in an increase in surface area, an increase in pore size, and a broadening of the pore size distribution. Third, pore size is affected by macroscopic compression of the polyimide composite. As evidenced in the examples below, pore size decreases with compression.

[0089] Yet another method of tuning the pore size is ion bombardment of the composite in either the polyimide or carbon state. The effect of ion bombardment depends on the method specified. For example, there is additive ion bombardment (e.g., CVD), where something is added and results in a decrease in pore size. There is also destructive ion bombardment, where the pore size increases. Finally, the pore size can be tuned (increased or decreased) by heat treatment in different gas environments, for example in the presence of carbon dioxide or carbon monoxide, chemically active environments, hydrogen reducing environments, etc. For example, a carbon dioxide environment, where in the case of activation mass is removed, the pore size increases, and the surface area increases, is known to make activated carbon. EXAMPLES

[0090] The following examples are offered for illustrative purposes only and are not intended to limit the scope of the various embodiments of the present invention in any way. Example 1: PI complexes

[0091] PI gels were made from pyromellitic dianhydride (PMDA) and 1,4-phenylenediamine (PDA) in a 1:1 molar ratio in DMAC solvent with target densities of 0.05g / cc (low density) and 0.125g / cc (high density). The precursors were mixed at room temperature for 3 hours, then acetic anhydride (AA) was added to the PMDA in a 4.3 molar ratio and mixed with the solution for 2 hours. Imidization was catalyzed with pyridine (Py).

[0092] To prepare the PI complex, the solution was cast in a Teflon container at a thickness of approximately 6 mm. The gel was allowed to harden at room temperature overnight and then subsequently cooled in supercritical CO. 2 The PI aerogel composite was pyrolyzed under inert atmosphere for 1 hour to carbonize it and form a monolithic PI composite. The lower target density PI (target density 0.05 g / cc) was pyrolyzed at 850 °C. The resulting carbon aerogel material had a density of 629.9 m. 2 The carbon aerogel material had a surface area of ​​553.8 m / g, a pore volume of 4.0 cc / g, and a pore diameter of 20.8 nm. The higher target density PI (0.125 g / cc) was pyrolyzed at 1050 °C. The resulting carbon aerogel material had a surface area of ​​553.8 m / g, a pore volume of 4.0 cc / g, and a pore diameter of 20.8 nm. 2 The porous structure parameters were determined by measuring the nitrogen adsorption isotherm (S) at −196 °C using a Quadrasorb gas sorption analyzer (Quantachrome Instruments, Boynton Beach, USA). BET -Surface area;V t -total pore volume). Pore width (nm) was estimated using the Barrett-Joyner-Halenda model. Samples were degassed at 100 mTorr and 60 °C for 12 h before analysis. Example 2: Sulfur doping of PI complexes

[0093] Each monolithic PI composite was ground into powder form. The resulting powdered PI material was mixed with sulfur powder in a ratio of 30:72 (wt%) and the mixture was ground for about 10 minutes. The sulfur and powdered PI mixture was then placed in a vial and annealed at 155°C for 12 hours in an Ar atmosphere. The resulting sulfur-doped carbon material contained about 70 wt% sulfur. Figures 3A and 3B show SEM images of the sulfur-doped carbon material. The sulfur-doped carbon aerogel material made from the lower target density PI (0.05 g / cc target density) had a melting point of 109 m. 2 The sulfur-doped carbon aerogel material made from the higher target density PI (0.125 g / cc) had a surface area of ​​29 m / g, a pore volume of 0.82 cc / g, and a pore diameter of 17.6 nm. 2 The surface area of ​​the porous structure was 0.12 cc / g, the pore volume was 0.12 cc / g, and the pore diameter was 12.4 nm. The parameters of the porous structure were calculated using the same method as in Example 1. Example 3: Electrodes made using sulfur-doped carbon materials

[0094] The sulfur-doped carbon material of Example 2 was dry-milled for 30 minutes, and then mixed with PVDF and Super C45 (conductive carbon) at 80 wt% of the sulfur-doped carbon material, 10 wt% of PVDF (polyvinylidene fluoride) and 10 wt% of Super C45 (conductive carbon) in N-methylpyrrolidone (NMP) (8:1:1 ratio) to make a slurry. The slurry was wet-milled for 30 minutes. The resulting slurry was coated on aluminum foil with a doctor blade and dried in vacuum for 12 hours. After drying, the areal mass loading of S was about 2 mg / cm. 2 The electrodes were obtained. Example 4: Half-cell units constructed from sulfur-doped carbon electrodes

[0095] A half-cell unit (2032 coin cells) was constructed using electrodes made according to Example 3 with lithium foil as the counter electrode and CELGARD 2500 as the microporous separator between the electrodes. The electrolyte was 1.0 M LiTFSI in dimethyl ether (DME) / 1,3-dioxolane (DOL) (weight ratio 1:1). FIG. 4A shows the capacity of the half-cell at 0.1 C for the first cycle of an electrode made from low density sulfur-doped carbon made according to the above example. FIG. 4B shows the capacity of the half-cell at 1 C for the first cycle of an electrode made from low density sulfur-doped carbon made according to the above example. FIG. 5A shows the capacity of the half-cell at 0.1 C for the first cycle of an electrode made from high density sulfur-doped carbon made according to the above example. FIG. 5B shows the capacity of the half-cell at 1 C for the first cycle of an electrode made from high density sulfur-doped carbon made according to the above example. Figure 6 shows the cycling performance of a half-cell of an electrode made from low density sulfur-doped carbon prepared according to the above examples, and Figure 7 shows the cycling performance of a half-cell of an electrode made from high density sulfur-doped carbon prepared according to the above examples. Alternative methods for producing PI aerogel

[0096] The preceding examples discussed herein teach specific methodologies for forming PI aerogels. In certain embodiments, the present invention also contemplates alternative methods for forming PI aerogels. A set of non-exhaustive and non-limiting examples of such alternative methodologies are now discussed.

[0097] For example, Suzuki et al., U.S. Patent No. 6,399,669 teaches four related methods of making PI dry gels (aerogels). In the first method, a PI precursor is synthesized, followed by formation of an imide from the PI precursor to produce a polyimide. A PI solution or swollen bulk is made, and the solution / swollen bulk is gelled to produce a PI wet gel. The wet gel is dried to obtain a PI dry gel (aerogel). In the second method, a PI precursor is synthesized, followed by formation of a PI precursor solution or swollen bulk. The solution / swollen bulk is gelled to produce a PI precursor wet gel. An imide is then formed from the PI precursor to form a PI wet gel. The wet gel is dried to obtain a PI dry gel (aerogel). In the third method, a PI precursor is synthesized, followed by formation of a PI precursor solution or swollen bulk. An imide is then formed from the PI precursor while gelling the PI precursor to produce a PI wet gel. In the third method, a PI precursor is synthesized, followed by formation of a PI precursor solution or swollen bulk. The solution / swollen bulk is gelled to produce a PI precursor wet gel, which is then dried to produce a PI precursor dry gel, which is then formed into an imide to produce a PI dry gel (aerogel).

[0098] As a further example, Leventis et al. [Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261] discuss the formation of PI aerogels using the ROMP method. A low molecular weight imidized oligomer end-capped with a polymerizable group is obtained and mixed with a polymerization (e.g., ROMP) catalyst. Polymerization is then initiated to produce a cross-linked polyimide. The polyimide is gelled and dried to form the PI aerogel. Leventis et al. [U.S. Pat. No. 9,745,198; Chidambareswarapattar et al., One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons, J. Mater. Chem., 2010, 20, 9666-9678] also report that acid teaches the formation of PI aerogels by mixing a dianhydride (e.g., PMDA) with an isocyanate (e.g., 4,4'-diisocyanatodiphenylmethane or methylenediparaphenyldiisocyanate) to form a sol-gel material. The sol-gel material is then dried to produce the PI aerogel. Leventis et al. [Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01. doi:10.1557 / opl.2011.90] also notes that DESMODUR N 3300A, DESMODUR RE, and MONDUR CD (all from BAYER CORP) can be utilized as isocyanates.

[0099] In another methodology, Guo et al. [Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane, ACS Appl. Mater. Interfaces 2011, 3, 546-552] synthesized aminosilsesquioxanes by: acid discuss the formation of PI aerogels by reacting with polyamic acid oligomers end-capped with anhydride groups. The product is imidized with pyridine (although thermal imidization is also conceivable), gelled, and subsequently dried to obtain PI aerogels. Nguyen et al. [Development of High Temperature, Flexible Polyimide Aerogels, American Chemical Society, proceedings published 2011] also reports the formation of PI aerogels by reacting with diamines and acid It has been described that a branched polyimide is produced by mixing dianhydrides, imidizing them, and then reacting them with a multi-amino compound (e.g., 1,3,5-tris(4-aminophenoxybenzene)). This product is then reacted with 4,4'-methylene diisocyanate and dried to form a PI-urea aerogel.

[0100] In another embodiment, Meador et al. [Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine, ACS Appl. Mater. Interfaces, 2012, 4(2), pp 536-544] report aciddiscusses the formation of PI gels by crosslinking polyamic acid oligomers end-capped with anhydride groups with aromatic triamines in solution followed by imidization. The resulting wet mass is dried to form PI aerogels. Furthermore, Meador et al. [Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels, ACS Appl. Mater. Interfaces 2015,7,1240-1249] discuss the formation of PI gels by crosslinking amine-capped oligomers with 1,3,5-benzenetricarbonyl trichloride. The resulting gel is dried to form PI aerogels.

[0101] In yet another embodiment, Pei et al. [Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383] prepared PI aerogels from polyimides containing trimethoxysilane side groups, which were the condensation products of polyimides containing acid chloride side groups and 3-aminopropyltrimethoxysilane. The resulting gel was dried to form the PI aerogel.

[0102] In any of these methods, a suspension of graphene can be added (see Zhang et al., Graphene / carbon aerogels derived from graphene crosslinked polyimide as electrode materials for supercapacitors, RSC Adv., 2015, 5, 1301).

[0103] Each of these methods can result in a polyimide aerogel, and the present invention contemplates any suitable method for producing such a polyimide aerogel. Regardless of which method is utilized to produce the PI aerogel, according to certain embodiments of the present invention, the resulting PI aerogel can be pyrolyzed to form a PI-derived carbon aerogel. Additives such as sulfur can be introduced as well, according to certain embodiments discussed herein.

[0104] All referenced publications are incorporated herein by reference in their entirety. Furthermore, if a definition or use of a term in a reference incorporated herein by reference is inconsistent with or contrary to the definition of that term provided herein, the definition of that term provided herein shall apply and the definition of that term in the reference shall be disregarded.

[0105] The above advantages, and those which will become apparent from the above description, are efficiently attained. Because certain changes can be made in the above construction without departing from the scope of the invention, it is intended that all matter contained in the above description or shown in the accompanying drawings shall be interpreted as illustrative and not in a limiting sense.

[0106] It is also to be understood that the following claims are intended to cover all of the general and specific features of the invention described herein, and all statements of the scope of the invention that may be said to lie therebetween as a matter of language. Some of the embodiments of the invention related to the present invention are given below. [Embodiment 1] 1. A sulfur-doped nanoporous carbon material comprising a pore structure, the pore structure comprising a fibril morphology and a series of pores surrounding elemental sulfur. [Embodiment 2] 1. A sulfur-doped nanoporous carbon material comprising: Pore ​​structure including fibril morphology; A Young's modulus of at least about 0.2 GPa, and A sulfur-doped nanoporous carbon material having a density of about 0.10 g / cc to about 1.5 g / cc. [Embodiment 3] 1. A sulfur-doped nanoporous carbon material, comprising: Pore ​​structure including fibril morphology; A conductivity of at least about 1 S / cm, and A nanoporous carbon material having a density of about 0.10 g / cc to about 1.5 g / cc. [Embodiment 4] 3. The nanoporous carbon material of embodiment 1 and / or embodiment 2, wherein the carbon material has a conductivity of at least about 1 S / cm. [Embodiment 5] The nanoporous carbon material of embodiment 1 and / or embodiment 3, wherein the carbon material has a Young's modulus of at least about 0.2 GPa. [Embodiment 6] 6. The nanoporous carbon material according to any one of embodiments 1 to 5, wherein the nanoporous carbon material comprises a carbon aerogel. [Embodiment 7] 7. The nanoporous carbon material of embodiment 6, wherein the carbon material comprises a polyimide-derived carbon aerogel. [Embodiment 8] The nanoporous carbon material of embodiment 6 and / or embodiment 7, wherein the carbon aerogel is in the form of a monolith or a powder. [Embodiment 9] 9. The nanoporous carbon material of embodiment 8, wherein the monolithic carbon aerogel is substantially or completely free of binder. [Embodiment 10] 8. The nanoporous carbon material of embodiment 6 and / or embodiment 7, wherein the monolithic carbon aerogel has a thickness of about 10 μm to about 1000 μm. [Embodiment 11] 11. The nanoporous carbon material according to any one of the preceding embodiments, wherein the pore structure is characterized by pores surrounding the sulfur. [Embodiment 12] 12. The nanoporous carbon material of embodiment 11, wherein the pores form an interconnected structure around the sulfur, characterized by a plurality of connection points between the sulfur and the pore walls of each pore in which the sulfur is surrounded. [Embodiment 13] 13. The nanoporous carbon material according to any one of the preceding embodiments, wherein the carbon material is doped with about 5%-90% sulfur by weight of the carbon material. [Embodiment 14] 14. The nanoporous carbon material according to any one of the preceding embodiments, wherein the carbon material has a pore volume of at least 0.3 cc / g. [Embodiment 15] 15. The nanoporous carbon material according to any one of the preceding embodiments, wherein the carbon material has a porosity of about 10% to about 90%. [Embodiment 16] 16. The nanoporous carbon material according to any one of the preceding embodiments, wherein the carbon material has a capacity of about 800 mAh / g to about 1700 mAh / g. [Embodiment 17] 17. The nanoporous carbon material according to any one of the preceding embodiments, wherein the pore structure comprises a full width at half maximum of about 50 nm or less. [Embodiment 18] 18. The nanoporous carbon material according to any one of the preceding embodiments, wherein the pore structure comprises a pore diameter at the maximum peak from the distribution of about 100 nm or less. [Embodiment 19] 19. The nanoporous carbon material of any one of the preceding embodiments, wherein the fibrillar morphology of the nanoporous carbon material comprises an average strut width of about 2-10 nm. [Embodiment 20] 1. A sulfur-containing monolithic polyimide-derived carbon aerogel composite formed from a nanoporous carbon material, the composite being binder-free and elemental sulfur is enclosed within the pores of the monolithic polyimide-derived carbon aerogel composite. [Embodiment 21] A current collector-less, binder-less, interconnected cathode material for lithium-sulfur batteries comprising an open-cell, monolithic, polyimide-derived nanoporous carbon aerogel having a fibril network and an array of pores, and elemental sulfur surrounded by the array of pores. [Embodiment 22] 21. An electrode comprising the nanoporous carbon material according to any one of the preceding embodiments 1 to 20. [Embodiment 23] 23. The electrode of embodiment 22, wherein the electrode is a cathode. [Embodiment 24] 24. The electrode of embodiment 23, wherein the cathode does not contain a separate current collector. [Embodiment 25] An electrochemical cell comprising the nanoporous carbon material according to any one of the preceding embodiments 1 to 20. [Embodiment 26] An electrochemical cell comprising the electrode according to any one of embodiments 22 to 24. [Embodiment 27] An energy storage device comprising the nanoporous carbon material according to any one of the preceding embodiments 1 to 20. [Embodiment 28] An energy storage device comprising an electrochemical cell according to embodiment 25 and / or embodiment 26. [Embodiment 29] 29. The energy storage device of any of embodiments 27 and 28, wherein the energy storage device is a battery. [Embodiment 30] 30. The energy storage device of embodiment 29, wherein the battery is a lithium-sulfur battery. [Embodiment 31] 1. A method for forming a continuous porous carbon-sulfur composite, comprising: providing a polyimide precursor; chemically or thermally imidizing the polyimide precursor; drying the imidized mixture to obtain a continuous porous polyimide; pyrolyzing the porous polyimide to obtain continuous porous carbon; and incorporating sulfur on or into said continuous porous carbon to obtain said continuous porous sulfur composite having a weight percent sulfur of greater than 0% but less than about 95% and a porosity of about 10% to about 90%. [Embodiment 32] 32. The method of embodiment 31, wherein the porous carbon sulfur composite is a monolith. [Embodiment 33] 32. The method of embodiment 31, wherein the porous carbon sulfur composite is free-standing. [Embodiment 34] 32. The method of embodiment 31, wherein the porous carbon sulfur composite is prepared on a substrate. [Embodiment 35] 35. The method of any one of embodiments 31-34, wherein the porous carbon sulfur composite is reinforced with a nonwoven material. [Embodiment 36] 35. The method of any one of embodiments 31-34, wherein the porous carbon sulfur composite is reinforced with a woven material. [Embodiment 37] 37. The method of any one of embodiments 31 or 34-36, wherein the porous carbon sulfur composite is micronized to form a powder. [Embodiment 38] 38. The method of any one of embodiments 31-37, wherein the polyimide wet gel composite is dried using subcritical and / or supercritical carbon dioxide to form the porous polyimide. [Embodiment 39] 39. The method of any one of embodiments 31-38, wherein the composite comprises an aerogel. [Embodiment 40] 40. The method of any one of embodiments 31-39, wherein the maximum pyrolysis temperature is from about 750°C to about 1600°C. [Embodiment 41] 41. The method of embodiment 40, wherein the porous carbon sulfur composite is graphitized to about 3000° C. [Embodiment 42] 40. The method of any one of embodiments 31 to 39, wherein the porous polyimide is preferably uniaxially compressed to increase its density. [Embodiment 43] 43. The method of embodiment 42, wherein the porous polyimide is compressed to a strain of as much as about 95%. [Embodiment 44] 43. The method of embodiment 42, wherein the porous carbon sulfur composite has a density tunable up to about 1.5 g / cc based on the amount of compression. [Embodiment 45] 45. The method of any one of embodiments 31-44, wherein the sulfur is incorporated onto or into the continuous porous carbon by melt infusion. [Embodiment 46] 46. ​​The method of any one of embodiments 31-45, wherein the sulfur is incorporated onto or into the continuous porous carbon by surface treating the continuous porous carbon with chemical functional groups that have an affinity for sulfur and polysulfides. [Embodiment 47] 47. The method of any one of embodiments 31-46, wherein the polyimide precursor comprises a diamine and a dianhydride in a suitable solvent. [Embodiment 48] 48. The method of embodiment 47, wherein at least one of the diamine and the dianhydride comprises an aromatic group. [Embodiment 49] The method of embodiment 47 and / or embodiment 48, wherein the suitable solvent comprises a polar aprotic solvent.

Claims

1. 1. A sulfur-doped nanoporous carbon material comprising: A nanoporous carbon aerogel material comprising a scaffold having a fibril morphology including nanostruts, nanorods, nanofibers, and / or nanofilaments, and having a network of a plurality of interconnected pores; and elemental sulfur contained within the network of interconnected pores of the nanoporous carbon aerogel material; The sulfur-doped nanoporous carbon material comprises: A Young's modulus of at least 0.2 GPa, and A density of 0.10 g / cc to 1.5 g / cc; The sulfur-doped nanoporous carbon material has the following properties:

2. 2. The sulfur doped nanoporous carbon material of claim 1, wherein the sulfur doped nanoporous carbon material has a conductivity of at least 1 S / cm.

3. 2. The sulfur doped nanoporous carbon material of claim 1, wherein the sulfur doped nanoporous carbon material comprises a polyimide derived carbon aerogel.

4. 2. The sulfur doped nanoporous carbon material of claim 1, wherein the nanoporous carbon aerogel material is in the form of a monolith or a powder.

5. 5. The sulfur-doped nanoporous carbon material of claim 4, wherein the nanoporous carbon aerogel material is binder-free when the nanoporous carbon aerogel material is in the form of a monolith.

6. 2. The sulfur doped nanoporous carbon material of claim 1, wherein the nanoporous carbon aerogel material has a thickness of 10 μm to 1000 μm when the nanoporous carbon aerogel material is in the form of a monolith.

7. 7. The sulfur doped nanoporous carbon material of claim 1, wherein the elemental sulfur is in the form of nanoparticles, and there are multiple connection points between the nanoparticles and the nanoporous carbon aerogel material.

8. 8. The sulfur-doped nanoporous carbon material according to claim 1, wherein the sulfur-doped nanoporous carbon material is doped with 5% to 90% sulfur by weight of the sulfur-doped nanoporous carbon material.

9. The sulfur doped nanoporous carbon material according to any one of claims 1 to 8, wherein the sulfur doped nanoporous carbon material has a pore volume of at least 0.3 cc / g.

10. 10. The sulfur doped nanoporous carbon material according to claim 1, wherein the sulfur doped nanoporous carbon material has a porosity of 10% to 90%.

11. The sulfur doped nanoporous carbon material according to any one of claims 1 to 10, wherein the sulfur doped nanoporous carbon material has a capacity of 800 mAh / g to 1700 mAh / g.

12. The sulfur-doped nanoporous carbon material according to any one of claims 1 to 11, wherein the nanoporous carbon aerogel material has a pore size distribution with a full width at half maximum of 50 nm or less.

13. 13. The sulfur-doped nanoporous carbon material according to any one of claims 1 to 12, wherein the nanoporous carbon aerogel material has a pore size at the maximum peak from the distribution of 100 nm or less.

14. 14. The sulfur doped nanoporous carbon material according to any one of claims 1 to 13, wherein the nanostruts, nanorods, nanofibers and / or nanofilaments have an average diameter of 2 to 10 nm.

15. A sulfur-containing monolithic polyimide-derived carbon aerogel composite comprising elemental sulfur and a monolithic polyimide-derived carbon aerogel, the sulfur-containing monolithic polyimide-derived carbon aerogel composite being binder-free and the elemental sulfur being contained within the pores of the monolithic polyimide-derived carbon aerogel.

16. 1. A binder-free cathode material for a lithium-sulfur battery, comprising: an open-cell, monolithic, polyimide-derived nanoporous carbon aerogel comprising a scaffold having a fibrillar network and having a network of interconnected pores; and elemental sulfur contained within said network of interconnected pores; a cathode material comprising:

17. An electrode comprising the sulfur-doped nanoporous carbon material according to any one of claims 1 to 14 or the sulfur-containing monolithic polyimide-derived carbon aerogel composite according to claim 15.

18. 20. The electrode of claim 17, wherein the electrode is a cathode.

19. 20. The electrode of claim 18, wherein the cathode does not include a separate current collector.

20. An electrochemical cell comprising the nanoporous carbon material according to any one of claims 1 to 14.

21. 20. An electrochemical cell comprising an electrode according to any one of claims 17 to 19.

22. An energy storage device comprising the nanoporous carbon material according to any one of claims 1 to 14.

23. 22. An energy storage device comprising an electrochemical cell according to claim 20 or 21.

24. 24. The energy storage device of claim 22 or 23, wherein the energy storage device is a battery.

25. 25. The energy storage device of claim 24, wherein the battery is a lithium-sulfur battery.

26. 1. A method for forming a continuous porous carbon-sulfur composite, comprising: mixing a polyimide precursor comprising an aromatic or aliphatic diamine and an aromatic or aliphatic dianhydride in a polar aprotic solvent; chemically or thermally imidizing the polyimide precursor to obtain a polyimide wet gel composite; drying the polyimide wet gel composite using subcritical and / or supercritical carbon dioxide to obtain a continuous porous polyimide; pyrolyzing the continuous porous polyimide to obtain a continuous porous carbon; and incorporating sulfur on or into said continuous porous carbon by melt injection or by surface treating said continuous porous carbon with chemical functional groups having an affinity for sulfur and polysulfides to obtain said continuous porous carbon-sulfur composite having a weight percentage of sulfur greater than 0% and less than 95% and a porosity of 10% to 90%; The method includes:

27. 27. The method of claim 26, wherein the continuous porous carbon sulfur composite is a monolith.

28. 27. The method of claim 26, wherein the continuous porous carbon sulfur composite is free-standing.

29. 27. The method of claim 26, wherein the open porous carbon sulfur composite is prepared on a substrate.

30. 30. The method of any one of claims 26 to 29, wherein the continuous porous carbon sulfur composite is reinforced with a nonwoven material.

31. 30. The method of any one of claims 26 to 29, wherein the continuous porous carbon-sulfur composite is reinforced with a woven material.

32. 32. The method of any one of claims 26 or 29-31, wherein the continuous porous carbon sulfur composite is pulverized to form a powder.

33. 33. The method of any one of claims 26 to 32, wherein the continuous porous carbon sulfur composite comprises an aerogel.

34. A method according to any one of claims 26 to 33, wherein the maximum pyrolysis temperature is from 750°C to 1600°C.

35. 27. The method of claim 26, wherein the continuous porous carbon-sulfur composite is graphitized at up to 3000°C.

36. 27. The method of claim 26, wherein the continuous porous polyimide is compressed to increase its density.

37. 27. The method of claim 26, wherein the continuous porous polyimide is uniaxially compressed to increase its density.

38. 38. The method of claim 36 or 37, wherein the continuous porous polyimide is compressed to a strain as high as 95%.

39. The continuous porous polyimide is compressed to increase its density or compressed uniaxially to increase its density; 27. The method of claim 26, wherein the continuous porous carbon sulfur composite has a tunable density up to 1.5 g / cc based on the amount of compression.

40. 27. The method of claim 26, wherein at least one of the diamine and the dianhydride comprises an aromatic group.

Citation Information

Patent Citations

  • Tin sulfide nanoparticle / graphene-polyimide based carbon aerogel composite material and preparation method thereof

    CN105731526A

  • Polyimide-based composite aerogel, controllable preparation method thereof and application of aerogel

    CN107365426A

  • Sulfur-doped hard carbon material, preparation method of same, and potassium ion battery with the hard carbon material being anode

    CN109301246A

  • Sulfur atom-doped carbon material using waste lithium-sulfur or magnesium-sulfur battery as raw material, and preparation and application thereof

    CN110697678A

  • Laser induced graphene materials and their use in electronic devices

    JP2017514783A